A Developed Management System for Site Usage of Construction Materials: A Case Study on Material Management in Construction Projects (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Good project management is essential. In many developing countries construction alone accounts for about 10 percent of gross national product, and 50 percent or more of the wealth invested in fixed assets. Material management is a management system that integrates purchasing, shipping and material control from suppliers. Based on those definitions, generally materials management can be defined as a process of planning, executing, and controlling the right source of materials with the exact quality, at the right time and place suitable for minimum cost construction process. Capability to coordinate and integrate purchasing, shipping and material control from suppliers is required for material cost control. The case study which is selected for this project of Godrej Rejuve at Keshavnagar Pune of RCC Building. First phase gives the Qualitative information regarding deviation in planned and actual materials in terms of S curve analysis using MSP tool and reasoning over the deviation is essential to know the effect of material planning before execution of project.